PENGARUH PROSES CRISPING PADA KUALITAS KESEGARAN TESPONG (Oenanthe javanica D. C) SELAMA MASA PENYIMPANAN - Muhammad Gilang Ramadhan; Sudaryanto Zain; Sarifah Nurjanah; Abdullah Md Zain; Roshita Ibrahim; Asri Widyasanti (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Water loss by transpiration causes withering in tespong (water celeries). Crisping can be considered to maintain the availability of water in tespong. The crisping is a process of diffusing water into vegetables through a soaking process by employing the mechanism of opening and closing of stomata and other natural openings which is influenced by surrounding temperature. The purpose of this study was to determine the effect of temperature and soaking time on the crisping process in maintaining the freshness quality of tespong. Tespong samples were immersed at 30°C and 40°C soaking temperatures for 3, 5, 7, and 10 minutes of soaking time, followed by a cooling process in cold storage at 5±2 °C for 16 hours before being stored in a chiller at 8±2°C for 4 days. Tespong’s weight loss, moisture content, color, and texture were observed during the storage time. As a control treatment, 2 groups of tespong were prepared. Control 1 was placed directly in a chiller with a temperature of 5±2°C whereas control 2 was in a laboratory room. The results showed that crisping treatment with 30°C soaking temperatures and 3 minutes soaking time gave better results in maintaining tespong’s freshness where weight loss, moisture content, L, a*, b*, and texture were -5.67%, 89.36%, 52.40, -14.54, 23.84, and 388.44 g/d, respectively.